A protocol for the integration of multi-omics bioinformatics: Mechanism of acupuncture as an adjunctive therapy for alcohol use disorder - Zhang, Peiming; Lan, Xiaochang; Fan, Baochao; Chen, Yiming; Wei, Xiaojing; Li, Xiangli; Fan, Ni; Tang, Chunzhi; Lu, Liming (Frontiers in Neurology, 2023)
Background Alcohol use disorder (AUD) has become a significant global factor in various diseases. As a non-pharmacological therapy, certain therapeutic potential has been found in acupuncture; however, in-depth mechanistic studies related to acupuncture for patients with AUD are still insufficient. Methods Based on a randomized control design and a multi-omics analysis plan, this protocol details the recruitment (42 AUD patients), group allocation (21 in acupuncture group vs. 21 in sham acupuncture group), intervention and follow-up (replacement drugs as a normal treatment, 2 weeks acupuncture duration, and 3 month follow-up), and data collection and analytical processes. For the clinical outcomes, in addition to the time required for alcohol withdrawal symptoms to subside as the primary outcome, changes in the alcohol withdrawal symptoms, alcohol craving, mood dysfunction, sleep disorder, fatigue, self-efficacy, gastrointestinal symptoms, the quality of life, and the relapse outcomes will be compared between the groups to confirm the acupuncture clinical effectiveness on alcohol withdraw. The gut microbiome and the fecal metabolomics will also be assessed to explore the association of the structure and the function of gut microflora and the mediation of acupuncture effect on AUD fully utilizing gut microflora multi-modal data and clinical information, via the combination of multi-omics methods, feature screening algorithms and appropriate models. Discussion The results of this study may help to strengthen clinical evidence of the mechanism of acupuncture intervention in patients with AUD, through understanding of the regulatory mechanism of acupuncture in the gut microbiome and its metabolism as well as AUD-related clinical manifestations. Trial registration Chinese Clinical Trial Registry ChiCTR2200058120. Registered on 24 Mar 2022.